2020 8th International Conference on Information and Communication Technology (ICoICT) 2020
DOI: 10.1109/icoict49345.2020.9166459
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Learning Management System Features based on Indonesian Higher Education National Standards using the Feature-Oriented Domain Analysis

Abstract: Various studies on the Learning Management System (LMS) have not examined the suitability of LMS features with the educational standards applicable in a country/region. This study aims to measure the suitability of LMS features with the National Higher Education Standards/ Standar Nasional Pendidikan Tinggi (SN-Dikti) in Indonesia using the Feature-Oriented Domain Analysis (FODA) method. This research identifies explicitly LMS features in the assignment and assessment functions. Besides, this study recommends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In addition, data collection was also intended to list features of the four systems of referred LMS. According to the listing result, as shown in Table 3, the features recorded in the previous studies referred to the FODA method that was used more than that of this research [1] because there were some features with the same functions that could be integrated. Table 4 presents the list of features of LMS references.…”
Section: Figure 1 Blended Learning Design In Lms Featurementioning
confidence: 99%
See 3 more Smart Citations
“…In addition, data collection was also intended to list features of the four systems of referred LMS. According to the listing result, as shown in Table 3, the features recorded in the previous studies referred to the FODA method that was used more than that of this research [1] because there were some features with the same functions that could be integrated. Table 4 presents the list of features of LMS references.…”
Section: Figure 1 Blended Learning Design In Lms Featurementioning
confidence: 99%
“…A learning management system (henceforth referred to as LMS) is utilized to present teaching materials and to help distribute class assignments to students effectively and efficiently. The utilization of LMS amidst the pandemic is deemed helping learning activities online [1] [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Widjajanti Wahyudin (2010), students' misconceptions about mathematics are influenced by their experiences in learning mathematics. Thus, how the mathematics teacher communicates concepts, structures, theorems, or mathematical formulas to students will affect students' descriptions of mathematics (Baskoro et al, 2006;Darmayanti, 2023;Wicaksono et al, 2020). Son (2015) revealed that mathematical communication skills are essential for a mathematics teacher as a facilitator and mediator in learning.…”
Section: Introductionmentioning
confidence: 99%